OLAHRAGA TRADISIONAL PACU PERAHU SEBAGAI MEDIA PENGUATAN KARAKTER GENERASI MUDA DAN PENGEMBANGAN SUMBER DAYA MANUSIA DUSUN RAWANG - Inggar Maizan; Nandia Pitri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Traditional sports are a vital component of cultural heritage, reflecting a community's identity. They are crucial for preserving cultural legacy and fostering character in the younger generation. One such sport, Pacu Perahu (Boat Racing), practiced in Rawang Hamlet, serves not only as a competition but also as a medium for character education and human resource development. Passed down through generations, it strengthens social solidarity and helps shape community character. However, social changes and modernization have led to declining youth participation in Pacu Perahu. This trend threatens to erode the character values inherent in the sport and undermines the potential of local culture-based character education, which is an effective means of shaping youth personality. This study aims to analyze the role of Pacu Perahu as a medium for strengthening youth character and to formulate revitalization strategies to ensure its relevance in modern character education. It further seeks to explore its contribution to human resource development in Rawang Hamlet. The findings are expected to provide a foundational framework for preserving Pacu Perahu and to contribute to youth character building. The research employs a qualitative approach using an ethnographic method.